Flexible support for multiple decision maker problems in regional biomass planning - Löfstedt R.; Sinclair P.; van der Horst D. (Comprehensive economic and spatial bio-energy modelling, 2002)
Over the last decade, the UK government has encouraged the development of biomass fuelled electricity plants. However, obtaining local planning permission has proved to be an important obstacle for the developers who won a government contract. On a number of occasions, local public opposition forced elected councillors to reject the proposal. These were examples of the typical siting controversy; local people were not involved in the original decision making (which took place at the national level), and rose to protest when they realised they may be exposed to the local disbenefits of the proposed plants. One of the most important questions which they felt was insufficiently answered was; why here? In response to these problems, the UK government is now trying out a regional approach to renewable energy. This approach combines target setting based on physical resource assessments with public consultations to develop a consensus on how and where within the region these targets should be met. Academies have developed Spatial Decision Support Systems (SDSS) to select the best fuel, technology, size and location for biomass power plants within a geographical area. This paper argues that such a System can be used to resolve siting controversies in the real world, but only if it is developed openly and interactively, in dialogue with the various stake-holders, rather than technology driven and top-down which has often been the case. Drawing on the considerable literature on risk communication and siting controversies, a number of best practice guidelines are proposed.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)